Keberadaan Bedbug dan Potensinya terhadap Kesehatan Manusia - Mirnawati Dewi; Defilia Anogra Riani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
In the 1970s bedbug infestation was thought to have disappeared, but since the 2000s, the appearance of bedbugs has been reported worldwide. Studies on bed bugs were carried out in several residential locations in Palangka Raya. This study aims to determine the existence of bed bugs in residential areas and the biological aspects of bed bugs. Survey and collection of bedbugs are carried out in densely populated areas. The results of the study showed that out of 20 houses observed, there were 2 houses that were identified with the presence of bed bugs. The only species of bed bug found is the, Cimex lecturarius. Bed bug infestation is observed in the beds. This shows that there is a potential for bed bugs to cause itching on the skin and allergic reactions in the occupants of the house. The population of bed bugs has the opportunity to spread to other residents' settlements.